The Confusion of Language Creativity in Labelling Millennial Business Unit in Public Spaces - Sahrul Romadhon (Buletin Al-Turas, 2020)
The purpose of this study was to document the confusion of the written language use development in the millennial era, especially in creative economic domains of business units, such as restaurants, coffee shops, cafes, or other millennial generation businesses. The study used a phenomenological qualitative research. The data of the research were business unit labels found in the public areas to attract the consumers. All labels of millennial business units were qualitatively analyzed using syntactic techniques. The research revealed various labels of business units as products of language creativity leading to language confusion. This was a phenomenon deliberately chosen by millennial business owners to get commercial value for consumers. Based on these findings, the research concluded that the labelling of millennial business units could be categorized into several variations, namely: 1) naming millennial business units with the absorption of foreign languages, 2) spelling, and 3) meaning. Therefore, the research suggests to conduct socialization to the millennial business unit owners about the rules of language uses in public spaces so that the existence of the Indonesian language and the commercial side could go hand in hand.